Uncovering gender bias in attitudes towards financial advisors - Klein, Galit; Shtudiner, Zeev; Zwilling, Moti (Journal of economic behavior & organization, 2021)
•The investment advice field has undergone a perceptual change with respect to the skills of female investment advisors and portfolio managers.•Female financial advisors report that they do not feel gender discrimination, although they represent only 20-30% of the investment house workforce.•There is a gap between the declarative level of respondents, who indicated that they do not view the gender of the advisor as having an influence on the quality of the investment, and the hidden level, where respondents’ preference for male over female advisors is still significant.•Respondents investing through investment houses showed a more egalitarian perception of female financial advisors. This study examines the effect of gender of financial advisors on the perception of the quality of investment advice. Based on expectation states theory (EST) as well as Social Role Theory (SRT), we aim to understand whether the perception of the quality of financial advice is affected by gender bias; that is, do people trust the ability of male financial advisors to earn profits more than female financial advisors’ ability to do so? To analyze our assessments, we interviewed female financial advisors and conducted two quantitative studies. The first quantitative study, in which 1,600 respondents participated, examined whether the financial advisor's gender impacts how subjects appraise the probability of success versus the level of loss. This was followed by a second study designed to examine the presence of hidden gender bias by applying a conjoint analysis model. The results, as reflected from the interviews, indicated that female financial advisors do not feel discriminated against by clients on the basis of gender. This finding is consistent with the results of the first quantitative study, which showed gender bias was latent and revealed only in particular cases, such as in the case of a high investment amount. However, the conjoint analysis results, which explored more hidden preferences, indicated that the advisor's gender is one of the most important factors influencing a consumer's decision when choosing an investment advisor. Hence, female advisors’ gender was found to have a negative effect on the desire to invest, and this negative attitude was found to be significantly higher among male respondents. Thus, the first study's result showed that when asked directly, participants are indifferent as to the financial advisor's gender, however, ideally people prefer male advisor over female, as shown in the second study. A summary of the findings shows that a perceptual change is still needed in order to reduce negative perceptions towards female advisors.